Impact of 100 LRRK2 variants linked to Parkinson's disease on kinase activity and microtubule binding - Kalogeropulou, Alexia F; Purlyte, Elena; Tonelli, Francesca; Lange, Sven M; Wightman, Melanie; Prescott, Alan R; Padmanabhan, Shalini; Sammler, Esther; Alessi, Dario R (Biochemical journal, 2022)
Mutations enhancing the kinase activity of leucine-rich repeat kinase-2 (LRRK2) cause Parkinson's disease (PD) and therapies that reduce LRRK2 kinase activity are being tested in clinical trials. Numerous rare variants of unknown clinical significance have been reported, but how the vast majority impact on LRRK2 function is unknown. Here, we investigate 100 LRRK2 variants linked to PD, including previously described pathogenic mutations. We identify 23 LRRK2 variants that robustly stimulate kinase activity, including variants within the N-terminal non-catalytic regions (ARM (E334K, A419V), ANK (R767H), LRR (R1067Q, R1325Q)), as well as variants predicted to destabilize the ROC:CORB interface (ROC (A1442P, V1447M), CORA (R1628P) CORB (S1761R, L1795F)) and COR:COR dimer interface (CORB (R1728H/L)). Most activating variants decrease LRRK2 biomarker site phosphorylation (pSer935/pSer955/pSer973), consistent with the notion that the active kinase conformation blocks their phosphorylation. We conclude that the impact of variants on kinase activity is best evaluated by deploying a cellular assay of LRRK2-dependent Rab10 substrate phosphorylation, compared with a biochemical kinase assay, as only a minority of activating variants (CORB (Y1699C, R1728H/L, S1761R) and kinase (G2019S, I2020T, T2031S)), enhance in vitro kinase activity of immunoprecipitated LRRK2. Twelve variants including several that activate LRRK2 and have been linked to PD, suppress microtubule association in the presence of a Type I kinase inhibitor (ARM (M712V), LRR (R1320S), ROC (A1442P, K1468E, S1508R), CORA (A1589S), CORB (Y1699C, R1728H/L) and WD40 (R2143M, S2350I, G2385R)). Our findings will stimulate work to better understand the mechanisms by which variants impact biology and provide rationale for variant carrier inclusion or exclusion in ongoing and future LRRK2 inhibitor clinical trials.